2017
DOI: 10.3892/or.2017.5617
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of expression of cancer stem cell markers and fusion gene in synovial sarcoma: Insights into histogenesis and pathogenesis

Abstract: Synovial sarcoma (SS) is an aggressive soft tissue tumor, with uncertain histological and cellular origin. SYT-SSX is considered to be responsible for sarcoma initiation and progression. The histogenesis and pathogenesis of this tumor are poorly understood, and prognosis of patients of SS is unsatisfactory. Recent studies have shown an association of cancer stem cells with the initiation and development of tumors. We explored immunohistochemical expression level of stem cell associated markers to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
(50 reference statements)
0
9
0
Order By: Relevance
“… 66 68 One interesting study revealed that breast CSCs originate from the fusion of M2-TAMs and breast cancer cells; these hybrid cells overexpress mesenchymal-associated genes and stemness markers. 48 Therefore, it can be said that tumor cells after EMT are likely becoming CSCs to some extent.…”
Section: Tumor Inflammatory Microenvironmentmentioning
confidence: 99%
“… 66 68 One interesting study revealed that breast CSCs originate from the fusion of M2-TAMs and breast cancer cells; these hybrid cells overexpress mesenchymal-associated genes and stemness markers. 48 Therefore, it can be said that tumor cells after EMT are likely becoming CSCs to some extent.…”
Section: Tumor Inflammatory Microenvironmentmentioning
confidence: 99%
“…The cellular plasticity (4), stem-like features (9,10), and unique genetics of SyS may explain its exceptional ability to escape immune surveillance despite the expression of immunogenic antigens. SyS is invariably driven by the SS18-SSX oncoproteinwhere the BAF subunit SS18 is fused to SSX1, SSX2 or, rarely, SSX4 (11).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer stemness originate from the fusion of TAM/M2 and breast cancer cells, these hybrid cells overexpress mesenchymal and cancer stemness markers [36] . Therefore, tumor cells are likely to become cancer stem cells after EMT process [37] . PD-1/PD-L1 induces immunosuppression and promotes EMT process of cancer cells.…”
Section: Discussionmentioning
confidence: 99%